Compost stew : an A to Z recipe for the earth - Siddals, Mary McKenna (Tricycle Press, 2010)
A rhyming text explains from A to Z, which common items around the house can be turned into the dark, crumbly stuff we call "compost stew". The collage illustrations are made from some of those items to help make the point. There's a note at the end of the text listing things that are not suitable for adding to the compost bin.